Analisis Kemandirian Peserta Didik pada Penerapan Kolase Daun dan Buah Pinus di Kelompok B TK Idhata Balakia Sinjai Barat - Syawaliah, Nurul Fajri; Yusuf T, M.; Hamansah, Hamansah (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The purpose of this study is to analyze the development of student independence in Idhata Balakia Kindergarten Sinjai Barat through the application of leaf and pine fruit collage, as well as identify supporting and inhibiting factors for its development. This study uses a descriptive qualitative research method. The data collection technique in this study uses observation, interviews and documentation. The informants in this study were 2 teachers and 10 students at Idhata Balakia Kindergarten. Data analysis techniques use data collection, data reduction, data presentation, and conclusion drawn. The way teachers increase the independence of group B students of Idhata Balakia Kindergarten is by doing good habits, setting a good example, and appreciating students so that they are more confident in what they are doing so that other students are motivated. The learning independence of group B students through the application of collage is in the category of Developing According to Expectations (BSH), this shows that collage activities can develop the learning independence of students to be able to carry out their own activities and be more confident in completing their tasks. The supporting and inhibiting factors for the development of students' independence are a supportive school environment with teachers and peers that provide positive encouragement for children and parents who still accompany their children in the classroom